2018
DOI: 10.1002/jsfa.9413
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Physalis peruviana calyces as a low‐cost valuable resource of phytoprostanes and phenolic compounds

Abstract: BACKGROUND: In Colombia, agro-industrial residues represent an enormous economic and environmental problem, which could be reduced if different techniques for the addition of value to such residues were implemented by this industrial sector. One of the fruits with the highest export rates is Physalis peruviana (goldenberry); however, this fruit is generally marketed without its calyx, generating a large amount of residues. To develop a strategy to add value to these residues, it is essential to know their chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 62 publications
0
18
0
1
Order By: Relevance
“…35 In almond kernels, the total PhytoPs concentration was in the range of 40.0−238.0 ng g −1 fw, 16 banana passion fruit shell samples (23180 ng g −1 dw), 36 in gulupa shell (67.6 ng g −1 dw), and gold berry 21659.8 ng g −1 dw. 37 The comparison of the level of PhytoPs in the various matrices allowed description of the total amount in rice grains that is in the range of most vegetable foods (being surpassed only by tropical fruits of high water content and scarce consumption rate), which revealed this matrix as an especially interesting source of PhytoPs in the diet, given the high naturalization in the rice and rice flour diets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…35 In almond kernels, the total PhytoPs concentration was in the range of 40.0−238.0 ng g −1 fw, 16 banana passion fruit shell samples (23180 ng g −1 dw), 36 in gulupa shell (67.6 ng g −1 dw), and gold berry 21659.8 ng g −1 dw. 37 The comparison of the level of PhytoPs in the various matrices allowed description of the total amount in rice grains that is in the range of most vegetable foods (being surpassed only by tropical fruits of high water content and scarce consumption rate), which revealed this matrix as an especially interesting source of PhytoPs in the diet, given the high naturalization in the rice and rice flour diets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The literature is scarce with respect to the plant parts of Physalis peruviana. However, in leaves, flavonoids such as quercetin, kaempferol and rutin were the most important secondary metabolites, while the main hydroxycinnamic acids detected were p-coumaric and caffeoyl-quinic acids [ 58 ]. Regarding Solanum muricatum , quercetin was the most important flavonoid, while ferulic and cinnamic acids were the most abundant phenolic acids detected [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, recent studies [68,116] identified PhytoPs and PhytoFs in coffee pulp, cocoa husk and pod husk residues and suggest to be valuable natural resources of PhytoPs and PhytoFs instead of chemically synthesizing them. Furthermore, Medina and co-workers [121,122,163] investigated the possible use of banana passion fruit shell waste as well as other tropical fruits (e.g. Passiflora edulis and Physalis peruviana) as natural sources of bioactive compounds including PhytoPs.…”
Section: Phytops As Oxidative Stress Biomarkersmentioning
confidence: 99%